1998
DOI: 10.1038/sj.jhh.1000709
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nitric oxide improves cyclosporin A-induced hypertension in rats and primates

Abstract: Cyclosporin-induced hypertension is a major complication of immunosuppression in transplant recipients but its pathophysiology is only partly understood. Cyclosporin reduces endothelium-dependent vasodilation and increases endothelin synthesis and release, which may contribute to this hypertension. We examined the effects of: (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…These agents may increase systemic vascular resistance and cause renal vasoconstriction through several mechanisms, including activation of vasoconstrictor factors, such as renin–angiotensin system, endothelin, and thromboxane A2, while reducing the production of vasodilator compounds, such as nitric oxide and prostacyclin [6–10]. Cyclosporin, but not tacrolimus, can also cause an early rise in sympathetic tone that may contribute to the acute elevation of blood pressure.…”
Section: Pathogenesis Of Post‐transplant Hypertensionmentioning
confidence: 99%
“…These agents may increase systemic vascular resistance and cause renal vasoconstriction through several mechanisms, including activation of vasoconstrictor factors, such as renin–angiotensin system, endothelin, and thromboxane A2, while reducing the production of vasodilator compounds, such as nitric oxide and prostacyclin [6–10]. Cyclosporin, but not tacrolimus, can also cause an early rise in sympathetic tone that may contribute to the acute elevation of blood pressure.…”
Section: Pathogenesis Of Post‐transplant Hypertensionmentioning
confidence: 99%
“…Several lines of evidence suggest that ET-1 plays a pivotal role in post-transplant hypertension [4][5][6]. In addition, it was reported that calcineurin inhibitors may interfere with nitric oxide (NO)-mediated vascular relaxation [7][8][9].…”
Section: Reduced Endothelin-1-and Nitric Oxide-mediated Arteriolar Tomentioning
confidence: 99%
“…Several lines of evidence suggest that ET-1 plays a pivotal role in post-transplant hypertension [4][5][6]. In addition, it was reported that calcineurin inhibitors may interfere with nitric oxide (NO)-mediated vascular relaxation [7][8][9].We were therefore interested in the question if increased vascular ET-1 and/or reduced nitric oxide could be shown to participate in post-transplant hypertensionassociated vascular dysfunction in patients. We tested the functional state of the vascular endothelin and NO system in vivo in renal allograft recipients with hypertension and matched healthy control subjects.…”
mentioning
confidence: 99%
“…Among the mechanisms leading to these side effects, various alterations in NO signalling pathway have been identified as key determinants for the development of renal and coronary vasculopathies [7,16,17]. The inhibition by CsA of the activity of a specific NO synthase (NOS) isoform, e.g., endothelial NOS (eNOS), was identified as a major trigger leading to vasodilatation impairments.…”
Section: Introductionmentioning
confidence: 99%